2006
DOI: 10.1099/vir.0.81558-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional integrity of the coxsackievirus B3 oriR: spacing between coaxial RNA helices

Abstract: The enterovirus oriR is composed of two helices, X and Y, anchored by a kissing (K) interaction. For proper oriR function, certain areas of these helices should be specifically oriented towards each other. It was hypothesized that the single-stranded nucleotides bridging the coaxial helices (Y-X and K-Y linkers) are important to determine this orientation. Spatial changes were introduced by altering the linker length between the helices of the coxsackievirus B3 oriR. Changing the linker lengths resulted in def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
(28 reference statements)
0
9
0
2
Order By: Relevance
“…However, subsequent studies have shown that this domain is interchangeable between PV, CVB4 and HRV14 (129). In addition, it was shown that the 3’NTRs of poliovirus, HRV14 and CVB3 are not required for infectivity (23, 156, 163). In contrast those of FMDV and EMCV are essential for viral viability (40, 132).…”
Section: Factors Involved In the Initiation Of Protein-primed Rna mentioning
confidence: 99%
“…However, subsequent studies have shown that this domain is interchangeable between PV, CVB4 and HRV14 (129). In addition, it was shown that the 3’NTRs of poliovirus, HRV14 and CVB3 are not required for infectivity (23, 156, 163). In contrast those of FMDV and EMCV are essential for viral viability (40, 132).…”
Section: Factors Involved In the Initiation Of Protein-primed Rna mentioning
confidence: 99%
“…The viral RNA‐dependent RNA polymerase 3D needs to bind the terminus of the 3′UTR to initiate minus strand RNA synthesis. Thus, the 3′UTR plays an important role in viral replication and pathogenesis (Melchers et al ., 1997; Mirmomeni et al ., 1997; van Ooij et al ., 2006). The CVB3 3′UTR contains three stem‐loops named X, Y and Z, where X and Y interact to form a ‘kissing pair’ tertiary structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It was possible that the low tolerance to mutation of CVB3 was caused by the presence of a lowerfidelity RNA-dependent RNA polymerase (RdRp) in terms of ribavirin incorporation, since at any given concentration of ribavirin, more mutagenesis would occur. To investigate this possibility, we purified the RdRps from both PV and CVB3 (12,32) and each was incubated with a previously described substrate (sym/ sub) and either the "correct" nucleotide or ribavirin triphosphate (RTP) (3,15). Examination of ribavirin incorporation revealed that CVB3 RdRp incorporated ribavirin much less efficiently than PV RdRp (Fig.…”
mentioning
confidence: 99%